DAYA SAING DAN PERMINTAAN EKSPOR PRODUK BIOFARMAKA INDONESIA DI NEGARA TUJUAN UTAMA PERIODE 2003-2012 - Irgandhini Agra Kanaya; Muhammad Firdaus (School of Business, Bogor Agricultural University (SB-IPB), 2014)
The world demand of herbal medicine is mounting. The more intensive effort is surely required in order to meet the supply of raw materials of medicinal products needed. The purposes of this research are to observe the competitiveness between countries in the world toward the provision of export products and also to analyze the affecting factors of export demand of medicinal products to the destination countries. The methods of analysis used in this research are Revealed Comparative Advantage (RCA), Export Product Dynamics (EPD), and Gravity Model. The analyzed period was an average of 2003 until 2012. The results of this research conclude that Indonesia has a good competitiveness in the commodity of turmeric and gaharu wood compared to the competitor countries based on the analysis of RCA and EPD, with the position of competitiveness of